Gambaran Peningkatan Informasi dan Sikap Wus dalam Pemeriksaan IVA Test di Wilayah Kerja Puskesmas Paringin Selatan - Wariyam, Wariyam; Yuliana, Fitri; Hidayat, Ahmad (Jurnal Rumpun Ilmu Kesehatan, 2024)
IVA test is one of the first steps to detect early cancer easily, cheaply, and can be done by midwives and provide immediate results, done visually using 3-5% vinegar acid. The low IVA test examination at the South Paringin Health Center from January to November 2022 of 82 WUS people or 1.89% % of the total WUS may be due to low information and negative WUS attitudes. This research method uses a descriptive method. With the population of all WUS in the working area of the South Paringin Health Center, precisely in Tarangan village in November 2022, using a saturated sample technique of 56 people. The results of the study found that 49 people (87.5%) had increased information in the good category and 56 people (100%) had a positive attitude.